The Effect of Lemon Aroma Therapy on Dysmenorrhoea Pain Scale in Adolescent Girls - Sukmawati, Ima; Noviati, Elis; Sekarwangi, Dewi (Nurul Ilmi : Journal of Health Sciences and Midwifery, 2024)
Introduction: Lemon aromatherapy is a way of relaxing the body that is also useful as a reduction in the pain scale during menstruation. Pain caused by intense uterine contractions and then an increase in prostaglandin levels that occurs in a woman is also known as dysmenorrhoea. The impact of dysmenorrhoea is pain, disruption of physical activity, and decreased learning achievement. A complementary therapy for dysmenorrhoea is lemon aromatherapy. The content of limeone itself has a function or benefit to inhibit prostaglandin levels from increasing so that the content of this limeon reduces the pain felt during dysmenorrhoea, besides that it can also improve emotionally. Objective: The purpose of this study to determine the effect of lemon aromatherapy on the dysmenorrhoea pain scale in class X adolescents at SMK Miftahussalam Ciamis. Method: The method used in this study used quantitative methods with experimental methods and used a one-group pre-test-post-test design on 40 respondents. The total population was 67 female students who experienced dysmenorrhoea during menstruation. Sampling using the accidental sampling method. Result: The results of this study used the Wilcoxon Sigend Rank Test with a meaning level of 95% and obtained a value of p-value 0.000 smaller than the significant value of 0.05. Where the pain scale before being given lemon aromatherapy was mostly in the mild pain category, as many as 20 (24.4%) respondents After giving lemon aromatherapy, the pain scale in respondents decreased by 27 (32.9%). Conclusion: Based on the results of research conducted at SMK Miftahussalam Ciamis, it was found that there was an effect of lemon aromatherapy on the dysmenorrhoea pain scale in class X adolescents at SMK Miftahussalam Ciamis because 0.000 <0.05.